AGRARIAN ENTREPRENEURSHIP AND INNOVATIVE METHODS OF ITS DEVELOPMENT - Nurgabylov Murat Nuriddinovich; Narbayeva Gulmira Kuanyshevna; Kuangaliev Tursunzada Kuangalia; Alimzhanova Gulimzhan Daulbaeva; Dosen Alma Sofiankatu (Academic Journal of Physical and Chemical Sciences, 2019)
Agrarian entrepreneurship is an important element in the development of agriculture and the immediate task of improving the innovation system of the agro-industrial complex of the Republic of Kazakhstan is to increase the agrarian innovation potential. According to the authors, in order for the innovative development of the agro-industrial complex of the RK to meet its purpose and justify the hopes placed on it in the foreseeable future, a full-fledged and comprehensive provision of this process is required, allowing it to overcome the features of its inertial and often stagnant and even regressive nature. This applies to all areas of the innovative development of the agro industrial complex of Kazakhstan. The introduction of IT technologies in Kazakhstan will not only increase the productivity of agricultural production, but also increase the competitiveness of agricultural products. Thanks to digitalization in developed countries, agriculture creates conditions for increasing production volumes, increasing the country’s export potential.